Parathyroidectomy Resolves Tooth Discoloration: A New Presenting Sign of Hyperparathyroidism? - Estella Musacchio; Andrea Piotto; Pierluigi Binotto; Antonio Toniato; Leonardo Sartori (Hindawi Limited, 2020)
Introduction. We report the resolution of tooth discoloration following parathyroidectomy in an otherwise asymptomatic woman with primary hyperparathyroidism-associated hypercalcemia. Case Report. A 59-year-old Caucasian woman, diagnosed with primary hyperparathyroidism in 2011, nonsmoker with excellent overall oral health. She complained of tooth discoloration starting in 2013. Pigmentation was particularly evident in the necks of the lower central and lateral incisors (Vita Classical score C2). No bleaching was undertaken. Parathyroidectomy was performed five years after primary hyperparathyroidism diagnosis. Six months later, a reduction in pigmentation was strikingly evident, with incisors scoring A1 and A2. The improvement persisted over time. Tooth value also increased compared to baseline. Conclusions. This is, to our knowledge, the first report that parathyroidectomy might resolve dental discoloration. This outcome deserves investigation in a meaningful sample size and may eventually prompt the inclusion of dental issues among the consequences of primary hyperparathyroidism.